THE PARTICIPATION OF THE PROSECUTION AUTHORITY IN CASES OF ADMINISTRATIVE OFFENCES (THE ECHR JUDGMENT IN THE CASE OF FIGURKA V. UKRAINE) - Samuliak, Mykhailo (Актуальні проблеми правознавства, 2025)
The issue of the prosecutor’s involvement has been repeatedly raised in Ukrainian courts in cases of administrative offences, including under Article 130 of the Code of Ukraine on Administrative Offences (hereinafter- CUAO). There is no consensus in the legal community in Ukraine on this issue. Consequently, the examination of the ECHR case law concerning the compliance of the legal framework regulating administrative proceedings under Article 130 of the CUAO with the principle of impartiality represents a pertinent and significant issue for the legal community. The volume of administrative cases under Article 130 of the CUAO within the judicial system is exceptionally large. This is the most common category of administrative offence cases. The purpose of the article is to analyse the case law of the ECHR concerning the compliance of the legal framework regulating administrative proceedings under Article 130 of the CUAO with the principle of impartiality. The analysis is conducted in the context of the absence of the prosecuting authority throughout the proceedings, with a particular focus on the case of Figurka v. Ukraine. In summary, the ECHR has recognized the legal framework regulating administrative proceedings under Article 130 of the CUAO as compliant with the European Convention on Human Rights, even in cases where the prosecuting authority was absent throughout the proceedings. The absence of the prosecutor from all court hearings does not, in itself, constitute a violation of the Convention. However, this does not necessarily mean that in every administrative offense case under Article 130 of the CUAO, where the prosecuting authority is absent throughout the proceedings, there is no breach of Article 6 § 1 of the Convention. I am convinced that the Figurka case should not be regarded as a final resolution on this matter.